2015
DOI: 10.17795/ijcp-3436
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Glioblastoma: A Case Report

Abstract: Introduction:Pituitary adenomas have been the most common sellaturcica tumors. There have been many unusual types of pituitary tumors that might neglect by radiologists and clinicians. One of these tumors would be the malignant glioma.Case Presentation:A 62-year-old male has complained from sudden frontal headache, nausea, vomiting, decreased vision, blurred vision and double vision. In skull radiographic, there was an expansion of sellaturcica and a lesion with clear border on T1; heterogeneous; iso - to hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Among five cases of hypothalamic/pituitary malignant gliomas described above, three resulted in the death of patients within a short period due to tumor progression or complications of surgical treatment (4,6,7). The outcomes of the other two patients were not reported (4,5). It should be noted that in our case, the patient is currently under chemotherapy.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Among five cases of hypothalamic/pituitary malignant gliomas described above, three resulted in the death of patients within a short period due to tumor progression or complications of surgical treatment (4,6,7). The outcomes of the other two patients were not reported (4,5). It should be noted that in our case, the patient is currently under chemotherapy.…”
Section: Discussionmentioning
confidence: 68%
“…Continuous tumor growth during cabergoline therapy revealed that the mass was not a prolactinoma; the rapid progression of tumor growth led to a suspicion of high-grade malignancy. In previously published clinical studies of endo-suprasellar malignant gliomas originating from the hypothalamic/pituitary axis, the clinical manifestations of tumors included acute neurological symptoms (vomiting and headache) (5,7), visual disorders (4-6), endocrine disorders (amenorrhea, galactorrhea, and diabetes insipidus) (4, 7), loss of appetite, and fatigue (4). Also, more invasive and larger tumors were detected in the primary MRI compared to our case.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, sellar GBM mimicked common sellar lesions, such as pituitary macroadenoma and/or craniopharyngioma; four cases underwent surgery via endoscopic endonasal surgery, and two cases underwent transcranial surgeries. Lemm et al ( 21 ) reported two cases with preoperative suspect of craniopharyngiomas; Mahta et al ( 22 ) and Anvari et al ( 23 ) reported in both cases the preoperative workup pointed toward the suspicion of a pituitary macroadenoma. The case reported by Deng et al ( 24 ) was a 42-year-old woman with an intra- and suprasellar not well-defined lesion, presenting headache, amenorrhea, diabetes insipidus, visual loss, and visual field defect.…”
Section: Discussionmentioning
confidence: 99%
“…46 Pituitary adenomas have traditionally been the most prevalent sellaturcica tumors, but malignant gliomas are one of the uncommon forms of pituitary tumors that may go unnoticed on a skull radiograph. 47 IDH1 mutations have been reported to associate with Glioma, AML, Ollier, and Maffucci syndromes. Based on the National Cancer Institute (NIH) GDC data portal, Mutant-IDH1-R132 has been reported in various primary resources, including the brain, hematopoietic and reticuloendothelial systems, prostate gland, bladder, breast, colon, liver, intrahepatic bile ducts, skin, bronchus and lung, connective and soft tissue, and thymus.…”
Section: Discussionmentioning
confidence: 99%